Children who are both wasted and stunted are also underweight and have a high risk of death: a descriptive epidemiology of multiple anthropometric deficits using data from 51 countries - Mark Myatt; Tanya Khara; Simon Schoenbuchner; Silke Pietzsch; Carmel Dolan; Natasha Lelijveld; André Briend (BMC, 2018)
Abstract Background Wasting and stunting are common. They are implicated in the deaths of almost two million children each year and account for over 12% of disability-adjusted life years lost in young children. Wasting and stunting tend to be addressed as separate issues despite evidence of common causality and the fact that children may suffer simultaneously from both conditions (WaSt). Questions remain regarding the risks associated with WaSt, which children are most affected, and how best to reach them. Methods A database of cross-sectional survey datasets containing data for almost 1.8 million children was compiled. This was analysed to determine the intersection between sets of wasted, stunted, and underweight children; the association between being wasted and being stunted; the severity of wasting and stunting in WaSt children; the prevalence of WaSt by age and sex, and to identify weight-for-age z-score and mid-upper arm circumference thresholds for detecting cases of WaSt. An additional analysis of the WHO Growth Standards sought the maximum possible weight-for-age z-score for WaSt children. Results All children who were simultaneously wasted and stunted were also underweight. The maximum possible weight-for-age z-score in these children was below − 2.35. Low WHZ and low HAZ have a joint effect on WAZ which varies with age and sex. WaSt and "multiple anthropometric deficits" (i.e. being simultaneously wasted, stunted, and underweight) are identical conditions. The conditions of being wasted and being stunted are positively associated with each other. WaSt cases have more severe wasting than wasted only cases. WaSt cases have more severe stunting than stunted only cases. WaSt is largely a disease of younger children and of males. Cases of WaSt can be detected with excellent sensitivity and good specificity using weight-for-age. Conclusions The category "multiple anthropometric deficits" can be abandoned in favour of WaSt. Therapeutic feeding programs should cover WaSt cases given the high mortality risk associated with this condition. Work on treatment effectiveness, duration of treatment, and relapse after cure for WaSt cases should be undertaken. Routine reporting of the prevalence of WaSt should be encouraged. Further work on the aetiology, prevention, case-finding, and treatment of WaSt cases as well as the extent to which current interventions are reaching WaSt cases is required.